Identification of Vibrio Spp. from Cultured Seabass Lates Calcarifer and Their Antibiogram Relationship with Plasmid Profiles - Chan, Soo Mun (1997)
Thirty eight bacteria isolates were recovered from seabass with vibrios is. These isolates were identified using the convention albiochemical tests and the API - 20E system. Most isolates were cream in colour, round, convex and entire. They were grouped into the genus Vibrio with the following traits: Gram-negative short rods, motile, positive catalase and oxidase reactions, fermentative metabolism towards Hugh and Leifson glucose medium and ferments D-glucose by producing acid but not gas. Yellow colonies (identified as Vibrio alginolyticus) and green colonies (identified as Vibrio parahaemolyticus) were obtained on TCBS agar. The API - 20 E test strips identified fifteen isolates as V. parahaemolyticus and twenty three isolates as V. alginolyticus. Comparative studies between